The impact of contextual relations on the semantic transformation of the verb - Diakho, Mouhamed (Journal of Arabic Language Sciences and Literature, 2024)
The research addressed the effect of contextual relations on the semantic transformation of the verb, based on the answer to the imaginary problem in the hadith: (Whoever stands on the Night of Decree out of faith and in the hope of reward, his previous sins will be forgiven), as the conditional verb (past) differs from the conditional verb (stands) in the future. The research concluded that the meaning of the temporal verb in the answer to the condition changed from the original to the future meaning, affected by (who), which makes it consistent with it. The temporal meaning of the verb may differ from the original due to contextual circumstances and different relations, which confirms that its formula is unable to accommodate all the fluctuations of its temporal meaning within the linguistic context.
Keywords: contextual relations; semantic shift; action; temporal significance